Influencia de la comunicación interna en el mejoramiento de la cultura organizacional de los trabajadores de la Municipalidad Provincial del Santa. - Castro Avila, Giuliana Lisset (2012)
This research work aims to present a set of theoretical tools and a case study analysis of internal communication of the Provincial Municipality of Santa, to propose a plan to improve internal communication so we can have a broader view of their impact on worker performance. The problem is formulated How internal communication influences the improvement of the organizational culture of the employees of the Municipality of Santa? , Which assumption is: Poor internal communication in an unfavorable influence on improving the organizational culture of the employees of the Municipality of Santa, affecting their work performance. Descriptive design was used, and the following methods: Deductive-inductive-synthetic and analytical statistics. The study population consisted of administrative staff working in the Public Services Management, Management of Works and Social Development Division of the Provincial Municipality of Santa. From which established a representative sample of 35 respondents, using probability sampling. Obtaining as a result of concern that the company still maintains a bureaucratic style of government where it is almost null empowerment workers, there is insufficient internal communication and therefore it affects users of services, with this area, presents major problems of internal communication. The identity of the company is seriously affected by poor internal communication, to the point that has led to an environment of mistrust prevails, compounded by the change of government policies and positions, which is only limited to a change of persons, but not old habits and / or forms of organizational management. They still use traditional media such as meetings or written within the same municipality and neglected other communication channels (including intranets and / or corporate email in this municipality are not utilized as they should). The least developed of the organization such as autonomy, structure and identity, influence on the low worker satisfaction with the quality, continuity and coordination of internal communication, and consequently decreases the satisfaction with the resolution of problems users. It recognized the importance of an environment conducive to job satisfaction, this research assessed the privacy, employee satisfaction, and environmental aspects, while the support of superiors and the degree of conflict with others as cultural factors organizational conditions are not conducive to work. It is therefore recommended to implement a Plan of Improvement of internal communication that contributes to drastically change the critical situation here evaluated, because of continuing this can cause great damage to the image of the municipality and the credibility of municipal management and its main objective increase cohesion among workers driving the corporate identity, increasing communication staff and ascending, intensifying communication tools to improve the organizational climate, which will affect the proper performance of the employees of the Municipality of Santa.